PATH FEASIBILITY AND MODIFICATION BASED ON THE PUMA 560 WORKSPACE ANALYSIS - SHAO, KC; YOUNG, KY (My University, 1994)
Robot paths are planned according to different industrial tasks. Their kinematic feasibility is restrained by the structure of the given robot manipulator. In order to design feasible paths under kinematic constraints and different task requirements, we propose first to utilize the geometry of the given robot to generate the geometric boundaries of different regions corresponding to kinematic constraints in the robot workspace. Geometric expressions are then derived to describe the relationship about the planned path and the robot workspace. Finally, by applying the developed modification strategies based on different task requirements, feasible paths can be obtained by modifying the infeasible portions of the paths. To demonstrate the proposed feasibility and modification schemes, the PUMA 560 robot manipulator is selected as a case study due to its complexity and practical application. The results are then extended to general wrist-partitioned types of industrial robot manipulators.